Electrochemical Detection and Spectrophotometry of Dopamine using Commercial Screen-Printed Electrodes - Eunike Thirza Hanita Christian; Basari Basari; Siti Fauziyah Rahman; Yudan Whulanza (Journal of Biomedical Science and Bioengineering, 2022)
Lab-on-chip is miniaturized devices integrated into a chip which can run one or several analyses which are usually done in laboratory settings, such as biochemical detection. Dopamine is an important neurotransmitter which regulates hormones, control of movement, emotion, attention, and motivation. Excess, lack, and dysregulation of dopamine could cause numbers of diseases and disorders. The technique used to measure and evaluate dopamine usually are expensive to run, require longer time to run, require some technical qualification to run, require expensive equipments, and some are invasive to do. These are the reasons why a lab-on-chip system is needed to make the detection of dopamine concentration faster, easier, and more portable. This paper studied the accuracy of using electrochemical detection to measure the concentration of liquid specimens of dopamine compared to uv/vis spectrophotometry. Electrochemical detection method named cyclic voltammetry was chosen for this study. The hypothesis for this study is that both peak current (ip) and absorbance positively correlate to concentration, therefore both could be used with minimal error margin. For this study, the peak current (ip) and absorbance of different concentrations of liquid specimen of dopamine are measured, and its regression were observed. It was shown that the concentration of liquid specimens of dopamine is linear to both anodic peak current (ipa) and absorbance. Due to the high R2 values of 0.9883, electrochemical detection could be used and implemented to detect dopamine concentration for application of lab-on-chip, as it is more portable and requires less volume of sample compared to spectrophotometry.